Oxidation of p-aminophenols and formal radical cyclization onto benzene rings: formation of benzo-fused nitrogen heterocycles. - Fletcher, S; Clive, D; Peng, J; Wingert, D (2005)
p-Iodophenol and its O-MOM-protected ether can be converted into iodoamines 2. These give cross-conjugated ketones 3 on oxidation with hypervalent iodides in the presence of methanol, and the ketones undergo radical cyclization. Exposure of the products to acid or sequential treatment with a Grignard reagent and acid effects rearomatization to produce benzo-fused nitrogen heterocycles 4.